Selection and consideration of vegetable species for architectural green-enveloping surfaces: a methodological instrument (2011)
The article expresses the need for a change in the comprehension and participation of architects towards the current urban environmental crisis. It enhances the importance of the city/nature relationship focusing on the ecological benefits that vegetable species bring on to architectural and urban projects, when considered as enveloping surface materials. Thus, the authors propose a methodological instrument comprised by two main components: the first one analyzes the requirements to take into account when including vegetable species as architectural enclosures (green roofs, walls and terraces); and the second one constitutes the matrix for accurately selecting those species, where, by means of simple adding operations, it allows for visualizing different varieties, their respectiveattributes and their final grading